Vincristine-Induced Cranial Neuropathy - TALEBIAN*, Ahmad; GOUDARZI, Razeieh; MOHAMMADZADEH, Mahdi; MIRZADEH, Azadeh Sadat (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Talebian A, Goudarzi RM, Mohammadzadeh M , Mirzadeh AS. Vincristine-Induced Cranial Neuropathy. Iran J Child Neurol. 2014 Winter; 8(1):66-68. Abstract Vincristine (VCR) is a vinca alkaloid that is used for treatment of many malignancies. The vinca alkaloids are neurotoxic, usually causing a peripheral neuropathy, but cranial neuropathies are rare as side effects. Described here is the case of a 2.5-year-old boy, a known case of Wilms’ tumor, treated by vincristine (0/067 mg/kg/day) and dactinomycin (0/045 mg/kg/day) after surgery. Three weeks after treatment, he presented with bilateral ptosis. Neurological examination revealed bilateral ptosis with normal pupillary reflex and eye movement. He received 3.015 mg cumulative dose of vincristine before development of ptosis. Treatment with pyridoxine (150 mg/m2 p.o. BID) and pyridostigmine (3 mg/kg p.o. BID) started as neuroprotective agents, and after 7 days the problem disappeared. The treatment continued for 6 weeks and there were no signs of ptosis or a recurrence in follow up 2 months later. References: Toopchizade V, Hosseini M, et al. Electrophysiological signs of neuropathy caused by vincristine. Medical Journal of Tabriz University of Medical Sciences. 2010 Autumn;31(3); 19-25. Gursel E.S. Vincristine-Induced Unilateral Ptosis in a Child. Pediatr Neurol 2009; 41:461-463. Ngamphaiboon N, Sweeney R, Wetzler M, Wang ES. Pyridoxine treatment of vincristine-induced cranial polyneuropathy in an adult patient with acute lymphocytic leukemia: Case report and review of the literature. Leuk Res. 2010 Aug;34(8):e194-6. Lash SC, Williams CP, Marsh CS, Crithchley C, Hodgkins PR, Mackie EJ. Acute Sixth-Nerve Palsy After Vincristine Therapy. Journal of AAPOS 2004 Feb;8(1): 67-8. Bay A, Yilmaz C, Yilmaz N, Oner AF. Vincristine induced cranial polyneuropathy. Indian J Pediatr. 2006 Jun;73(6):531-3. Tuxen M K, Hansen SW. Complication of treatment, Neurotoxicity secondary to antineoplastic drugs. Cancer Treatment Reviews 1994;20:191-214. Ozyurek H, Turker H, Akbalik M, Bayrak AO, Ince H, Duru F. Pyridoxine and pyridostigmine treatment in vincristine-induced neuropathy. Pediatr Hematol Oncol. 2007 Sep;24(6):447-52. Duman O, Tezcan G, Hazar V. Treatment of vincristineinduced cranial polyneuropathy. J Pediatr Hematol Oncol. 2005 Apr;27(4):241-2. Müller L, Kramm CM, Tenenbaum T, Wessalowski R, Göbel U. Treatment of vincristine-induced bilateral ptosis with pyridoxine and pyridostigmine. Pediatr Blood Cancer. 2004 Mar;42(3):287-8. Dejan S, Dragana B, Ivana P, Borivoje B, Marko P. Vincristine induced unilateral ptosis. J Pediatr Hematol Oncol. 2009 Jun;31(6):463.